Study on Performance Improvement and Economical Aspect of Gas Turbine Power Plant Using Evaporative Cooling System - Alam, Hilman Syaeful; Sasso, John; Djunaedi, Imam (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2015)
The study is intended to improve the performance of gas turbine engines in order to meet both electrical power demand and peak load in the power plant. In this paper, evaporative cooling system had been applied to improve the performance of gas turbine in Pesanggaran power plant in southern Bali Island, Indonesia. Moreover, the economic analysis was conducted to determine the capacity cost, operating cost and payback period due to the investment cost of the system. Based on the evaluation results, the power improvement for the three gas turbine units (GT1, GT2 and GT3) are 2.09%, 1.38%, and 1.28%, respectively. These results were not very significant when compared to the previous studies as well as on the aspects of SFC (Specific Fuel Consumption), heat rate and thermal efficiency. Based on the evaluation of the economic aspects, the reduction of production costs due to the application of evaporative cooling system was not economical, because it could not compensate the investment cost of the system and it resulted a very long payback period. These unsatisfactory results could be caused by the high relative humidity. Therefore, further studies are needed to investigate the other alternative technologies which are more suitable to the climate conditions in Indonesia.